Stimuli‐Responsive Optical Nanomaterials - Li, Zhiwei; Yin, Yadong (Advanced materials (Weinheim), 2019)
Responsive optical nanomaterials that can sense and translate various external stimuli into optical signals, in the forms of observable changes in appearance and variations in spectral line shapes, are among the most active research topics in nanooptics. They are intensively exploited within the regimes of the four classic optical phenomena—diffraction in photonic crystals, absorption of plasmonic nanostructures, as well as color‐switching systems, refraction of assembled birefringent nanostructures, and emission of photoluminescent nanomaterials and molecules. Herein, a comprehensive review of these research activities regarding the fundamental principles and practical strategies is provided. Starting with an overview of their substantial developments during the latest three decades, each subtopic discussion is led with fundamental theories that delineate the correlation between nanostructures and optical properties and the delicate research strategies are elaborated with specific attention focused on working principles and optical performances. The unique advantages and inherent limitations of each responsive optical nanoscale platform are summarized, accompanied by empirical criteria that should be met and perspectives on research opportunities where the developments of next‐generation responsive optical nanomaterials might be directed. Responsive optical nanomaterials have attracted long‐standing research interests owing to their promise in both fundamental studies and practical applications. The current research activities on responsive optical nanomaterials are reviewed, with special focus on optical diffraction, absorption, refraction, and emission. Perspectives are also provided to point out the possible directions for future research.